The role of stress in symptom exacerbation among IBS patients - Blanchard, Edward B.; Lackner, Jeffrey M.; Jaccard, James; Rowell, Dianna; Carosella, Ann Marie; Powell, Catherine; Sanders, Kathryn; Krasner, Susan; Kuhn, Eric (Journal of psychosomatic research, 2008)
Over 200 treatment-seeking irritable bowel syndrome (IBS) patients completed 4 weeks of daily prospective measures of stress and gastrointestinal symptoms as well as retrospective measures of stress (life events over 12 months, hassles over 1 month). We also obtained the stress measures on 66 nonill controls. Irritable bowel syndrome patients report more frequent hassles than controls and a greater stress impact than controls. Using structural equation modeling, we found that the data were consistent with a model of robust autocorrelation effects of both week-to-week gastrointestinal (GI) symptom indices ( r=.84) and stress indices ( r=.73), as well as strong concurrent effects of stress on IBS symptoms ( r=.90) and vice versa ( r=.41). The data also were consistent with a model where there were effects of stress in Week t upon GI symptoms in Week t+1 and t+2, but they were mediated through the concurrent week effects and/or autocorrelation effects. There were no statistically significant independent pathways from stress in Week t to GI symptoms in Week t+1 or t+2. Thus, there is more support for a reciprocal relation between stress and symptoms than there is for a causal relation.